2016
DOI: 10.1038/nature21022
|View full text |Cite
|
Sign up to set email alerts
|

Reversible methylation of m6Am in the 5′ cap controls mRNA stability

Abstract: Internal bases in mRNA can be subjected to modifications that influence the fate of mRNA in cells. One of the most prevalent modified bases is found at the 5′ end of mRNA, at the first encoded nucleotide adjacent to the 7-methylguanosine cap. Here we show that this nucleotide, N6,2′-O-dimethyladenosine (m6Am), is a reversible modification that influences cellular mRNA fate. Using a transcriptome-wide map of m6Am we find that m6Am-initiated transcripts are markedly more stable than mRNAs that begin with other n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
1,054
7
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 862 publications
(1,145 citation statements)
references
References 59 publications
25
1,054
7
2
Order By: Relevance
“…al. also provided evidence that m 6 A demethylation is mediated by Alkbh5 (48). Our m 6 A-seq data raise the possibility that Gsk-3 activity could be directly or indirectly regulating Alkbh5, in addition to FTO.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…al. also provided evidence that m 6 A demethylation is mediated by Alkbh5 (48). Our m 6 A-seq data raise the possibility that Gsk-3 activity could be directly or indirectly regulating Alkbh5, in addition to FTO.…”
Section: Discussionmentioning
confidence: 69%
“…While this manuscript was in preparation, data from Jaffrey and colleagues was published showing that FTO does not specifically demethylate m 6 A RNA, but instead prefers to demethylate m 6 A m (48 6 A relied on an antibody against m 6 A, but this antibody was shown to detect both m 6 A and m 6 A m (49). In addition, while the approach we used for m 6 A-seq did not provide us with the precise locations of demethylated adenosines in RNA from Gsk-3 DKO ESCs, we nonetheless observed hundreds of mRNAs had regions largely devoid of methylated adenosines.…”
Section: Discussionmentioning
confidence: 99%
“…As for RNA methylation, five types of methylation have been identified including N 7 ‐methylguanine (m 7 G at the 5' cap), N 6 ‐methyl adenosine (m 6 A), N 1 ‐methyl adenosine (m 1 A), 5‐methylcytosine (m 5 C), and 2‐ O ‐methylation (2'OME). Additionally, di‐methylation occurs when a combination of two different methylations affect the same mRNA, such as when m 6 Am is observed next to the 5' cap (Mauer et al., 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The researchers found that mRNAs with this mark -called m 6 Am -are more stable because their caps are harder to remove 16 . "It's exciting to people that the landscape of potentially regulated messenger RNA modifications that might influence gene expression could be an order of magnitude more complex than we thought before, " Gilbert says.…”
Section: Mining For More Marksmentioning
confidence: 99%
“…Jaffrey's work 16 suggests that FTO, which He identified as an m 6 A eraser, actually targets m 6 Am. And in October, He's group reported 17 that the enzyme Xiao flagged as a 6 mA eraser on DNA actually does a better job of stripping m 1 A off a particular type of RNA.…”
Section: Mining For More Marksmentioning
confidence: 99%